Fallen angels - Myers, Walter Dean, 1937- (New York Scholastic Inc., 1988)
Seventeen-year-old Richie Perry, just out of his Harlem high school, enlists in the Army in the summer of 1967 and spends a devastating year on active duty in Vietnam.
Keywords: Vietnamese Conflict, 1961-1975 -- Juvenile literature; African Americans -- Fiction; Vietnamese Conflict, 1961-1975 -- Fiction